Did the Saudi Economic Growth distributed equally - Arabi, Khalafalla Ahmed Mohamed; Kunna, Elwalied Nourelhuda; Al-Suhaimi, Qassem Mazal (Technium Social Sciences Journal, 2022)
Based on the four available household surveys from 1999 to 2018, this paper answers the main reach question: did Saudi economic growth spread evenly?. The aforementioned question was answered using the nonlinear autoregressive distributed lag model (NARDL) to account for the possibility of nonlinear effects of the explanatory variables on the dependent variable. The Gini coefficient is the dependent variable explained by real per capita income, squared real per capita income to examine the Kuznets inverted U shape hypothesis, and lastly the inflation rate. The results demonstrate that exogenous variables account for 99 percent of the variation in the dependent variable. The estimated coefficients are highly significant including the squared per capita implying the validity of the Kuznets hypothesis. The results have policy implications in that the economic growth path that began in the 1950s has had an impact on income and consumption magnitude in the Kingdom of Saudi Arabia, where economic policies such as free education and health services, exemption from income tax, Zakat distribution, and regulation of charity societies support the average Saudi family and reduce inequality. Jazan and Najran will need to put in even more effort to catch up to the other districts.